In-Car Suffocating Prevention Using Image Motion Detection - Ikhwan Hafiz, Muhamad; Fairuz Rizal, Mohamad Rashidi (2013)
Child left unattended in a car until they are suffocated has become a common issue today. A video-based system to automatically check whether there are any human left in the car when the engine has been turned off is proposed to solve this problem. A simple edge and motion detection technique has been used in order to detect human inside the car.